Words from the dialect of the Bani Amer tribe (Al-Mallha) in the Gaza StripA semantic study (مجلة إحالات, 2026)
Dialects are among the pivotal issues that have gained popularity among linguists, and modern studies have been conducted around them, which have benefited the linguistic lesson in one way or another. Therefore, this research seeks to document words from the dialect of the Bani Amer (Al-Malha) tribe in the  Gaza Strip and study its implications by referring to the origins of the books of the Arabic linguistic heritage, by talking with a brief introduction about the Bani Amer (Al-Malha) tribe in Palestine, and then takingsamples from the spoken words when The Bani Amer tribe in the Gaza Strip, with a focus on giving examples of the context of each word to reach the proper linguistic connotation, and then talking about thewords that are unique to the Bani Amer tribe (Al-Malha) in the Gaza Strip in Palestine, which arecharacterized by their meanings and connotations used by the sons of Arab Bani Amer, with the arrangement of words according to the alphabetical system, and clarifying all of the aboveusing the descriptive-analytical approach, and then the conclusion of the research, which includes the results and recommendations, themargins of the research and the index of sources and references.